Foot and Ankle Somatosensory Deficits Affect Balance and Motor Function in Children With Cerebral Palsy - Zarkou, Anastasia; Lee, Samuel C. K.; Prosser, Laura A.; Jeka, John J. (Frontiers in Human Neuroscience, 2020)
Sensory dysfunction is prevalent in cerebral palsy (CP). Evidence suggests that sensory deficits can contribute to manual ability impairments in children with CP, yet it is still unclear how they contribute to balance and motor performance. Therefore, the objective of this study is to investigate the relationship between lower extremity (LE) somatosensation and functional performance in children with CP. Ten participants with spastic diplegia (Gross Motor Function Classification Scale: I-III) and who are able to stand independently completed the study. Threshold of light touch pressure, two-point discriminatory ability of the plantar side of the foot, duration of vibration sensation, and error in joint-position sense of the ankle were assessed to quantify somatosensory function. Balance was tested by the Balance Evaluation System Test (BESTest) and postural sway measures during a standing task. Motor performance was evaluated by using a battery of clinical assessments: 1) Gross Motor Function Measure (GMFM-66-IS) to test gross motor ability, 2) spatiotemporal gait characteristics (velocity, step length) to evaluate walking ability, 3) Timed Up and Go (TUG) and 6 Min Walk (6MWT) tests to assess functional mobility, and 4) an isokinetic dynamometer was used to test the Maximum Volitional Isometric Contraction (MVIC) of the plantarflexor muscles. The results showed that the light touch pressure measure was strongly associated only with the 6MWT. Vibration and two-point discrimination were strongly related to balance performance. Further, vibration sensation of the first metatarsal head demonstrated a significantly strong relationship with motor performance as measured by GMFM-66-IS, spatiotemporal gait parameters, TUG, and ankle plantarflexors strength test. Joint position sense of the ankle was only related with one subdomain of the BESTest (Postural Responses). This study provides preliminary evidence that LE sensory deficits can possibly contribute to the pronounced balance and motor impairments in CP. The findings emphasize the importance of developing a thorough LE sensory test battery that can guide traditional treatment protocols toward a more holistic therapeutic approach by combining both motor and sensory rehabilitative strategies to improve motor function in CP.